Targeting Carbonic Anhydrases with Fluorescent BODIPY-Labelled Sulfonamides - Waghorn, P; Jones, M; McIntyre, A; Innocenti, A; Vullo, D; Harris, A; Supuran, C; Dilworth, JR (2012)
In the pursuit of dual-mode imaging agents of the tumour hypoxia markers carbonic anhydrases (CA) IX and XII, sulfonamides 4-(2-aminoethyl) benzenesulfonamide and 1,3,4-thiadiazole were functionalised with a 4,4-difluoro-4-borata-3a-azonia-4a-aza-s-indacene (BODIPY) dye to afford fluorescent aromatic sulfonamide conjugates as potential agents for simultaneous positron emission tomography and fluorescence imaging. Both compounds exhibited nanomolar potency as inhibitors of four CA isoforms: the cytosolic CA I and II, and the transmembrane CA IX and XII. Cell uptake experiments with a CA IX positive and null cell line showed no uptake with the 1,3,4-thiadiazole species in either cell line, whilst the benzenesulfonamide species showed uniform internalisation in both cell lines that limited these compounds as selective imaging agents. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.